Efektivitas Inovasi Terhadap Peluang dan Perkembangan Kewirausahaan: Sistematik Literature Review - Dessy Hesrhanty; Selli Agustin (Majalah Ilmiah Manajemen STIE Aprin Palembang, 2024)
The objective of this research is to gain a deeper understanding of the meaning of creativity and its role in generating opportunities and developing business ventures. This study employs a qualitative method with a systematic literature review approach. The research data consist of articles published in national journals. The collected data were analyzed using thematic analysis. The findings indicate that a high level of creativity in a business whether in products, services, or other marketing aspects—contributes significantly to the efficiency and organizational structure of the company.